Suggestology and Suggestopedia The Theory of the Lozanov Method - Bancroft, W. Jane. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
In "Suggestologiia," Georgi Lozanov discusses his theories of Suggestology, the scientific study of suggestion, and Suggestopedia, the application of suggestion to pedagogy. The Lozanov thesis cannot properly be understood in isolation, however, and Suggestology and Suggestopedia should be considered in relation to yoga, Soviet and Western work in suggestion and psychotherapy, the Russian school of physiological psychology and the Soviet concept of the unconscious, Soviet linguistics and pedagogy. Suggestology investigates the subsensory signals or subliminal stimuli which come from the physical or social environment and which are absorbed into the unconscious mind before receiving a conscious expression. Suggestion, especially spoken suggestion, activates the reserve capacities of the mind or the memory. Suggestopedia increases memorization capacities. Hypermnesia is facilitated by relaxation techniques (derived from yoga and autogenic therapy) which increase the subject's suggestibility to spoken suggestions or unconscious stimuli. The principal theoretical elements of Suggestopedia are: authority, infantilization, double-planeness, intonation, rhythm, and concert pseudo-passivity. The lack of scientific data in "Sugestologiia" may lead to a negative reaction to the Lozanov thesis. The right way to approach the thesis, however, may be to translate the underlying original ideas and to reconstruct the statistical evidence in accordance with the more rigorous and less ideologically oriented methods used in Western science. (Author/AM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Environment; Cognitive Processes; Educational Innovation; Educational Psychology; Educational Theories; Hypnosis; Language Instruction; Learning Activities; Learning Processes; Memorization; Memory; Psychological Studies; Psychotherapy; Recall (Psychology); Retention (Psychology); Second Language Learning; Teaching Methods; Lozanov Method -- Suggestology; Hypermnesia -- Lozanov (Georgi) -- Suggestopedia -- Yoga; Reports, Research